The effect of gamma-ray irradiation on the electrical conductivity of CuO-PbO glasses - Yavuz, Hulusi; Kaygili, Omer (Taylor & Francis Ltd, 2011)
The effect of gamma-ray irradiation on the dc electrical conductivity of CuO-PbO glasses has been studied as a function of temperature. A 33% CuO-67% PbO glass composition has been prepared, using the melt-quenching technique. The samples have been irradiated to a dose of 0.5 MGy using a Co-60 gamma-source. The electrical conductivity of this glass composition was investigated before and after gamma-ray irradiation. The values of the dc electrical conductivity have been measured from 303 to 373 K, and the activation energy of samples before and after gamma irradiation has been calculated. The observed data show that the electrical conductivity increases with temperature and following gamma irradiation. The electrical conductivity of CuO-PbO can be interpreted in terms of mixed ionic-electronic conduction.
Keywords: CuO-PbO glasses; dc electrical conductivity; gamma-irradiation effects